Electrical and thermal transport properties of spark plasma sintered n-type Bi2Te3−xSex alloys: the combined effect of point defect and Se content. Issue 40 (24th August 2015) - Pan, Yu; Wei, Tian-Ran; Wu, Chao-Feng; Li, Jing-Feng
Abstract : Investigation of electrical and thermal transport properties in powder-processed Bi2 Te3− x Se x thermoelectric alloys determined the optimal composition based on defect chemistry. Abstract : Performance enhancement can be realized in p-type Bi2 Te3 but hardly in n-type Se-modified Bi2 Te3 alloys fabricated by powder processing as compared with conventional ingots. To reveal the reasons and investigate the optimal Se content in fine-grained n-type Bi2 Te3− x Se x materials processed by mechanical alloying (MA) and spark plasma sintering (SPS), the amount of Se was varied in a wide range and electrical transport properties were investigated and discussed in association with the results of Hall measurements. Thermal transport properties were also studied with Raman spectra. It is revealed that different concentrations of point defects are induced by changing the Se content x from 0 to 1.0 in Bi2 Te3− x Se x . The point defects and their interaction (including donor-like effects) not only largely change the carrier concentration and mobility, but also enhance the phonon scattering that would lead to a decrease of thermal conductivity. Consequently, the optimal composition is confirmed as Bi2 Te2.2 Se0.8 with a corresponding carrier concentration of 4.5 × 10 19 cm −3 and a maximum ZT value of 0.82 at 473 K, approximately 35% increased than that obtained at optimal Bi2 Te2.7 Se0.3 conventionally used for ingots. This work indicates that the point defects as well as their interaction during MA and SPS shift the optimal Se content from traditional x = 0.3 to x = 0.8 in n-type Bi2 Te3− x Se x, demonstrating the importance of comprehensive control of point defects by adjusting the Se content for different processes.